Variedades de governos de coalizão no presidencialismo: Chile , 1990-2010 - Huneeus,Carlos (2012)
The article analyzes the coalition governments in Chile during four Presidential terms under the Concertación de Partidos por la Democracia [Alliance of Parties for Democ] (1990-2010) and focuses attention on the roles of the Presidents and the parties. The analysis considers the context of the political system, because presidents do not act alone, but with their cabinets, and do not stand alone, since they must consider the other institutions (state and para-state) that limit their decision-making autonomy. The article also analyzes the institutional architecture and Presidential leadership, a combination of factors that has previously received little attention in studies on Presidentialism in LatinAmerica, andwhich deservesmore in-depth study, since the centralized decisions under Presidentialism vary according to each president's style. This is demonstrated through an analysis of the organization of Presidents Patricio Aylwin, Eduardo Frei Ruiz-Tagle, Ricardo Lagos, and Michelle Bachelet. This institutional order includes four government administrations with their own particularities (coalition government in the case of the first three and that of a single party in the latter), explainable according to their different presidential styles and their different relations with the parties.